The impact of stock options on risk-taking: Founder-CEOs and innovation - Michael Hickfang; Ulrike Holder (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2018)
This paper investigates whether and how founder-CEOs' risk incentives (VEGA) are related to firm innovation. We exploit a change in the accounting treatment of stock-based compensation under FAS 123R in 2005 to show a relationship between founders' risk-taking incentive and innovation. Using a sample of 226 firm-year observations between 2002 and 2008, we first show that stock options are incentives that encourage founder-CEOs to engage in risk-taking behaviour and that these were significantly reduced as a result of FAS 123R. Secondly, we find that innovation activities of the observed firms are significantly declining due to the reduction of the option compensation and the associated reduction in VEGA of founder-CEOs. Finally, our difference-in-differences approach provides strong evidence that there is a relationship between CEOs risk-taking and innovation output. Our results imply that even in founder-led firms it is important to incentivise founders' risk-taking behaviour in order that firms continue to innovate and remain competitive. – – Diese Studie untersucht, ob und wie Risikoanreize (VEGA) von Gründervorstandsvorsitzenden mit Unternehmensinnovationen zusammenhängen. Wir nutzen eine Änderung in der Bilanzierung von aktienbasierten Vergütungen nach FAS 123R in den USA im Jahr 2005, um den Zusammenhang zwischen Risikoanreizen und Innovationen aufzuzeigen. Anhand von 226 Firmen-Jahr-Beobachtungen zwischen 2002 und 2008 zeigen wir, dass Aktienoptionen Anreize sind, die Gründervorstandsvorsitzende zu mehr Risikobereitschaft ermutigen. Wir finden, dass die Innovationsaktivitäten der beobachteten Firmen durch Reduzierung der Optionsvergütung und damit einhergehende Risikoverminderung der Gründervorstandsvorsitzenden signifikant rückläufig sind. Vor allem unser Differenz-von-Differenzen-Ansatz lässt den Rückschluss zu, dass eine Beziehung zwischen Risikoanreizen und Innovationsoutput besteht. Folglich implizieren unsere Resultate, dass es auch bei gründergeführten Unternehmen wichtig ist, das Risikoverhalten der Gründer zu fördern, damit Unternehmen weiterhin innovativ und wettbewerbsfähig bleiben.
Keywords: G30; G32; G38; D80; O31; 650